2017
DOI: 10.1371/journal.pone.0168930
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hypoxic and Hypercapnic Ventilatory Response in Healthy Volunteers

Abstract: IntroductionA previous study has suggested that the Human Leukocyte Antigen (HLA) allele DQB1*06:02 affects hypoxic ventilatory response (HVR) but not hypercapnic ventilatory response (HCVR) in an Asian population. The current study evaluated the relationship in Caucasians and Asians. In addition we assessed whether gender or polymorphisms in genes participating in the control of breathing affect HVR and HCVR.MethodsA re-breathing system was used to measure HVR and HCVR in 551 young adults (56.8% Caucasians, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Another study not restricted to healthy volunteers included patients in an emergency room and did not exclude smokers, also found higher SpO 2 in females (0.7% higher in African American females and 0.6% higher in white females) . Recently, a study whose primary goal was to explore genetic factors related to the control of breathing, unexpectedly found higher SpO 2 in women compared to men. The difference between sexs was similar to our findings (98.0% ± 1.3% in females vs 96.6% ± 1.7% in males).…”
Section: Discussionmentioning
confidence: 99%
“…Another study not restricted to healthy volunteers included patients in an emergency room and did not exclude smokers, also found higher SpO 2 in females (0.7% higher in African American females and 0.6% higher in white females) . Recently, a study whose primary goal was to explore genetic factors related to the control of breathing, unexpectedly found higher SpO 2 in women compared to men. The difference between sexs was similar to our findings (98.0% ± 1.3% in females vs 96.6% ± 1.7% in males).…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea increases the tidal volume and thus normalizes the arterial saturation. As the reaction of the respiratory center on hypoxemia can differ, other patients will not react on hypoxemia and not become dyspneic [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the primary driver of inhalation is a mechanism called "hypercapnic ventilatory drive", and "hypoxic ventilatory drive" is a secondary, back-up mechanism that stimulates breathing. (Dick, 1997, Goldberg, 2017 Hypercapnic drive forces exhalation in a very powerful, deep brain stem, primordial reflex. This is easily demonstrated in a typical individual who wishes to hold their breath for more than a minute.…”
Section: Respiratory Physiology Hypoventilation and Hypercapniamentioning
confidence: 99%